High-toughness steel-concrete interface adhesive and preparation method thereof
By using hollow fiber-loaded corrosion inhibitors in steel-concrete interface adhesives, a three-dimensional network structure and chemical protection mechanism are formed, solving the problem of insufficient toughness and durability of adhesives and achieving efficient stress dispersion and corrosion protection.
Patent Information
- Application Number
- CN202511633804.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-10
- Publication Date
- 2026-01-02
AI Technical Summary
Existing steel-concrete interface adhesives have insufficient durability, poor toughness and impact resistance under long-term humid and hot conditions, and are prone to internal stress concentration and interface delamination.
A high-toughness steel-concrete interface adhesive using hollow fiber loaded with corrosion inhibitors improves the toughness and durability of the adhesive through the synergistic effect of the three-dimensional network structure toughening and corrosion inhibitors.
It significantly improves the fracture toughness, impact resistance and fatigue resistance of the adhesive layer, prevents the interface from peeling off due to stress concentration, extends service life and prevents corrosion.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of building construction materials, and particularly relates to a high-toughness steel-concrete interfacial adhesive and a preparation method thereof. BACKGROUND
[0002] In modern road and bridge and building structure engineering, steel-concrete composite structure has become a vital structure form, which firmly combines steel plate and concrete through adhesive, fully utilizes the respective advantages of high tensile strength of steel and good compressive performance of concrete, and significantly improves the bearing capacity, stiffness and durability of the structure. This interfacial adhesive is widely used in bridge deck pavement, building structure reinforcement (such as steel-bonded reinforcement of beams, plates and columns), tunnel pavement and other composite pavements, and is used for interlayer bonding between concrete (or steel plate) and asphalt concrete. Its core function is to effectively prevent pavement from moving, falling off, deforming and other diseases when the structure bears external load, especially in the working condition where the horizontal thrust increases due to high temperature, and to ensure the long-term safe and stable operation of the transportation infrastructure.
[0003] At present, the steel-concrete interfacial adhesives used in engineering can be mainly divided into various types according to their systems. Common ones include two-component steel-bonding glue with epoxy resin as matrix, the A component of which usually contains epoxy resin (such as E-51 or E-44), toughening agent and filler, and the B component contains curing agent (such as polyamide or amine) and coupling agent for promoting adhesion. These adhesives usually need to add additives such as defoaming agent, leveling agent, filler (such as quartz powder, silica powder) and the like to optimize the construction performance and material performance.
[0004] Although the existing adhesive technology has been widely applied, they still have some obvious technical defects and limitations. First, the durability of the bonded structure is challenged, and the performance of traditional epoxy resin-based adhesives may deteriorate in long-term hot and humid aging environment, although high-performance products can meet the standard requirements, but their long-term stability in more severe environment still needs to be further improved. Second, the toughness and impact resistance of the existing adhesives often need to be strengthened, especially when dealing with the difference in expansion coefficient caused by drastic temperature change and the vibration and fatigue stress brought by traffic load, the adhesive layer is easy to produce internal stress concentration, if the toughness of the material is insufficient, microcracks are easy to be initiated and gradually expanded, eventually leading to interface peeling or damage of the pavement.
[0005] Therefore, it has become an urgent technical requirement in the field of current road and bridge engineering and building structure reinforcement to develop a new type of adhesive with higher toughness, better durability and effective coordination of the interface stress between steel and concrete. SUMMARY
[0006] To this end, it is necessary to provide a high-toughness steel-concrete interface adhesive and a preparation method thereof to solve the problem of weak toughness and easy separation of the existing steel-concrete bonding interface.
[0007] To achieve the above object, the present application provides a high-toughness steel-concrete interface adhesive, comprising the following components by weight: epoxy resin matrix 90-110 parts, curing agent 15-30 parts, toughening agent 10-25 parts, filler 30-60 parts, hollow fiber 0.2-2 parts, and corrosion inhibitor 0.5-2 parts.
[0008] Further, the corrosion inhibitor is loaded on the hollow fiber.
[0009] Further, the corrosion inhibitor is at least one of molybdate or phosphate.
[0010] Further, the length of the hollow fiber is 100-200 μm.
[0011] Further, the material of the hollow fiber is polyester, polypropylene or polyamide.
[0012] Further, the filler includes quartz sand and silica fume, the particle size of the quartz sand is 60-80 μm, and the particle size of the silica fume is 10-30 μm.
[0013] Further, the curing agent is polyamide or modified amine curing agent.
[0014] Further, the toughening agent is at least one of carboxyl-terminated nitrile rubber and polyurethane prepolymer.
[0015] Another aspect of the present application discloses a preparation method of the steel-concrete interface adhesive as described above, comprising the following steps: S1. Resin matrix preparation: blending the epoxy resin matrix and the toughening agent in an organic solvent and stirring uniformly; S2. Filler dispersion: adding the filler to the mixture obtained in step S1 and stirring uniformly; S3. Fiber and corrosion inhibitor dispersion: adding the hollow fiber and the corrosion inhibitor to the mixture of step S2 and stirring until uniformly dispersed; S4. Curing reaction: adding the curing agent and stirring until uniform.
[0016] Further, in step S3, the hollow fiber is subjected to immersion treatment in the liquid corrosion inhibitor to load the corrosion inhibitor on the fiber, and then the treated hollow fiber is added to the mixture of step S2 and stirred until uniformly dispersed.
[0017] Further, in step S3, the immersion treatment time is 30-60 minutes.
[0018] The technical scheme has the following beneficial effects: The hollow fiber is first applied in the steel-concrete structural bonding field with extremely high performance requirements. The hollow fiber is not a simple filler in the bonding agent, but plays a multiple key mechanical enhancement role: Three-dimensional network toughening effect: the hollow fiber forms a uniform three-dimensional network structure after the bonding agent is cured. When the bonding layer generates microcracks due to external load (such as traffic vibration) or internal stress (such as thermal expansion and cold contraction), the fiber can generate a "bridging effect", effectively inhibiting the further expansion of the crack and dispersing the concentrated stress to a larger area. This is fundamentally different from the traditional rigid filler which only improves hardness. The present application significantly improves the fracture toughness, impact resistance and fatigue resistance of the bonding layer.
[0019] In the stress process, in addition to the bridging effect, the special structure of the hollow fiber allows it to absorb and disperse energy through micro-deformation of the cavity wall when subjected to compression or shear stress, thereby enabling the bonding agent of the present application to effectively adapt to the large difference in expansion coefficient between steel and concrete and dynamic load, preventing brittle peeling of the interface due to stress concentration, and greatly improving the safety margin and service life of the bonding interface. DETAILED DESCRIPTION
[0020] The present application discloses a high-toughness steel-concrete interfacial bonding agent, which comprises the following components by weight: epoxy resin matrix 90-110 parts, curing agent 15-30 parts, toughening agent 10-25 parts, filler 30-60 parts, hollow fiber 0.2-2 parts, and corrosion inhibitor 0.5-2 parts.
[0021] In some embodiments, the corrosion inhibitor is loaded on the hollow fiber.
[0022] Once the traditional bonding agent cracks, the corrosion medium will reach the steel plate surface along the crack, causing corrosion, and the process is irreversible. The corrosion inhibitor contained in the conventional bonding agent cannot achieve long-term corrosion resistance.
[0023] The present application preloads the corrosion inhibitor on the hollow fiber. When the microcrack expands and penetrates the fiber, the fiber lumen breaks, the internal corrosion inhibitor is released and quickly transported to the steel substrate crack interface where protection is most needed, forming a protective film. The corrosion inhibitor quickly takes effect.
[0024] The toughening effect of the hollow fiber reduces the generation and width of the crack, physically delaying the invasion of the corrosion medium; and the active corrosion protection of the corrosion inhibitor chemically eliminates the risk of rust even after the generation of a small crack. The two are not simply added, but form a synergistic protection mechanism of "physical barrier" and "chemical inhibition", which jointly solves the technical problem of insufficient durability of the steel-concrete interface in harsh environments.
[0025] In some embodiments, the corrosion inhibitor is at least one of molybdate or phosphate.
[0026] In some embodiments, the hollow fiber has a length of 100-200 μm.
[0027] In some embodiments, the hollow fiber is made of polyester, polypropylene or polyamide.
[0028] In some embodiments, the filler includes quartz sand and silica fume, the quartz sand has a particle size of 60-80 μm; the silica fume has a particle size of 10-30 μm.
[0029] In some embodiments, the curing agent is polyamide or modified amine curing agent.
[0030] In some embodiments, the toughening agent is at least one of carboxyl-terminated nitrile rubber or polyurethane prepolymer.
[0031] A preparation method of the steel-concrete interface adhesive as described above, comprising the following steps: S1. Resin matrix preparation: blend the epoxy resin matrix with the toughening agent in an organic solvent, and stir until uniform; S2. Filler dispersion: add the filler to the mixture obtained in step S1, and stir until uniform; S3. Fiber and corrosion inhibitor dispersion: add the hollow fiber and the corrosion inhibitor to the mixture of step S2, and stir until uniformly dispersed; S4. Curing reaction: add the curing agent, and stir until uniform.
[0032] In some embodiments, in step S3, the hollow fiber is subjected to immersion treatment in the liquid corrosion inhibitor, so that the corrosion inhibitor is loaded on the fiber, and then the treated hollow fiber is added to the mixture of step S2, and stirred until uniformly dispersed.
[0033] In some embodiments, in step S3, the immersion treatment time is 30-60 minutes.
[0034] To describe the technical content, structural features, purposes and effects of the technical solutions in detail, the following embodiments are described in detail.
[0035] Example 1: (1) Hollow fiber loaded molybdate corrosion inhibitor (hollow fiber 1 part, corrosion inhibitor 1 part) Reagent: weigh the sodium molybdate powder, dissolve in deionized water, and prepare a 5% molybdate solution.
[0036] Procedure: Take 150 μm polyester hollow fibers, completely immerse in the above sodium molybdate aqueous solution. Soak at room temperature for 60 minutes, with 2-3 times of slight stirring to ensure full infiltration. After taking out, place in an oven at 80°C for 2 hours to dry, so that the water is completely evaporated, and sodium molybdate crystals are deposited and loaded inside the fiber cavity and on the surface.
[0037] (2) Preparation of the adhesive Formulation (by weight): Bisphenol A type epoxy resin (E-51): 100 parts; Carboxyl-terminated butyl nitrile rubber (CTBN, toughening agent): 15 parts; Acetone (solvent): 15 parts; Polyamide (curing agent): 20 parts; Quartz sand (particle size -70 μm): 35 parts; Silica fume (particle size -20 μm): 15 parts; The above pretreated hollow fibers: 2 parts.
[0038] Preparation procedure: The bisphenol A type epoxy resin, CTBN toughening agent and acetone solvent are added to a stirred tank, and mechanically stirred at a speed of 300 rpm for 15 minutes until the system becomes a homogeneous transparent mixture.
[0039] The quartz sand and silica fume fillers are added, and the stirring speed is increased to 400 rpm, and stirring is continued for 50 minutes to ensure that the fillers are fully wetted and uniformly dispersed, without visible agglomerates.
[0040] The hollow fibers loaded with sodium molybdate are added, and low-speed stirring (150 rpm) is used for 75 minutes, in order to uniformly disperse the fibers in the colloid, while avoiding excessive shear forces that would damage the fiber structure.
[0041] The polyamide curing agent is added, and the stirring speed is adjusted to 250 rpm, and stirring is continued for about 5 minutes to ensure uniform distribution of the curing agent.
[0042] A high-toughness steel-concrete interface adhesive according to the present application is prepared.
[0043] Example 2 Formulation (by weight): Bisphenol A type epoxy resin (E-51): 90 parts; Carboxyl-terminated butyl nitrile rubber (CTBN, toughening agent): 20 parts; Acetone (solvent): 15 parts; Polyamide (curing agent): 30 parts; Quartz sand (particle size -70 μm): 15 parts; Silica fume (particle size -20 μm): 15 parts; The above pretreated hollow fiber: 1 part.
[0044] The preparation steps are the same as in Example 1.
[0045] Example 3 Formulation (by weight): Bisphenol A type epoxy resin (E-51): 110 parts; Carboxyl-terminated butyl nitrile rubber (CTBN, toughening agent): 25 parts; Acetone (solvent): 20 parts; Polyamide (curing agent): 15 parts; Quartz sand (particle size -70 μm): 35 parts; Silica ash (particle size -20 μm): 25 parts; The above pretreated hollow fiber: 4 parts.
[0046] The preparation steps are the same as in Example 1.
[0047] Comparative Example 1 (without any fiber) Except that no fiber is added, the remaining components (corrosion inhibitor is mixed directly), amounts and preparation steps are exactly the same as in Example 1.
[0048] Comparative Example 2 (with solid fiber) Replace the "polyester hollow fiber loaded with molybdate" in Example 1 with solid polyester fiber of the same weight, length and material, and the solid fiber is not treated with any corrosion inhibitor. The remaining components, amounts and preparation steps are exactly the same as in Example 1.
[0049] Comparative Example 3 (with hollow fiber but not loaded with corrosion inhibitor) Use the same polyester hollow fiber as in Example 1, but only soak it in the same amount of deionized water for 60 minutes (simulate the pretreatment process but without corrosion inhibitor), and after taking it out, also dry it at 80°C for 2 hours. The remaining components, amounts and preparation steps are exactly the same as in Example 1.
[0050] Performance testing of the adhesives prepared in the above examples and comparative examples 1. Adhesive strength test Test piece preparation: one side of the steel plate (such as Q235 steel, size 40mm x 40mm x 5mm) is sandblasted, and the concrete block (strength grade C50, size 40mm x 40mm x 40mm) is prepared. A layer of adhesive about 2mm thick is coated between the treated surface of the steel plate and the concrete surface, and cured and maintained as required (such as 25°C, relative humidity 50%, maintenance for 7 days) to produce a tensile shear test piece.
[0051] Test method: Using a universal testing machine. The loading rate is 2 mm / min, and the maximum load at the time of specimen failure is recorded.
[0052] Calculation: Adhesive strength (MPa) = maximum load (N) / adhesive area (mm2). Five specimens are tested for each group of data, and the average value is taken.
[0053] 2. Toughness (impact resistance) test Specimen preparation: Same as the adhesive specimen for the adhesive strength test.
[0054] Test method: Drop hammer impact test. The specimen is fixed horizontally, and a steel ball with a mass of 500g is allowed to fall freely from a height of 30cm to impact a specific location near the adhesive area of the specimen.
[0055] Result evaluation: Immediately after impact, observe and record the damage to the adhesive layer and the interface area.
[0056] Excellent: Only minor indentation or no visible cracks in the adhesive layer (expected result for Example 1).
[0057] Good: Obvious short cracks appear, but the cracks do not penetrate (possible result for Comparative Examples 2 and 3).
[0058] Poor: Long and wide radial cracks appear, or even partial peeling (possible result for Comparative Example 1).
[0059] 1. Corrosion resistance test (salt spray test) Specimen preparation: Sandblast one side of a steel plate (size 100mm x 50mm x 5mm), then evenly apply 1mm thick adhesive. Before the adhesive layer is cured, use a sharp blade to draw an "X" shaped notch on the center of the steel plate, which penetrates the surface of the steel plate. The curing conditions are the same as before.
[0060] Test method: Place the prepared specimen with the notch into a salt spray test chamber. The test conditions are: 5% NaCl solution, chamber temperature 35°C, continuous spraying.
[0061] Result evaluation: After 72 hours of salt spray test, remove the specimen, gently rinse with clean water and dry, and observe the rusting condition at the edge of the notch. Use a microscope or magnifying glass with a scale to measure the maximum width (mm) of the rusting expansion at the edge of the notch. The smaller the rusting width, the better the corrosion resistance.
[0062] Test results are shown in Table 1 below.
[0063] Table 1. Test results of adhesive performance The adhesive strength and impact resistance of Examples 1-3 are significantly better than those of Comparative Examples 1 and 2, proving that the addition of hollow fibers plays a key role in toughening and enhancing the adhesive strength, effectively transmitting and dispersing stress and preventing brittle failure.
[0064] The corrosion resistance of Examples 1-3 is far better than that of Comparative Example 3, proving that the hollow fibers loaded with corrosion inhibitor (BTA) play a role in corrosion protection. When the adhesive layer is damaged by scratching, the corrosion inhibitor on the fibers can be released and inhibit corrosion, while the hollow fibers of Comparative Example 3 do not have this function. The corrosion width of Comparative Examples 1 and 2 is greater than 2 mm, proving that the "simple mixing" method of corrosion inhibitor is inefficient. The corrosion width of Example 1 is less than 0.5 mm, which strongly proves the high efficiency and durability of the hollow fiber loading method of the present application.
[0065] It should be noted that the relational terms herein such as first and second and the like are used solely to distinguish one from another entity or action, without necessarily requiring or implying any actual relationship or order between such entities or actions. Moreover, the terms "comprises", "comprising", or any other variations thereof, are intended to cover a non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements does not include only those elements but can include other elements not expressly listed or inherent to such process, method, article, or apparatus. An element proceeded by "comprises... a" does not, without more constraints, exclude the existence of additional elements of the process, method, article, or apparatus that comprises the element. Additionally, the terms "a" and "an" are understood to encompass the plural, unless the context clearly dictates otherwise. Furthermore, to the extent that the terms "includes", "including", "has", "having" or variations thereof are used in either the detailed description or the claims, such terms are intended to be inclusive in a manner similar to the term "comprising".
[0066] Although the above-mentioned embodiments have been described, those skilled in the art can make further changes and modifications to the embodiments once they know the basic inventive concept, so the above description is only an embodiment of the present application and does not limit the patent protection scope of the present application. Any equivalent structure or equivalent process transformation made by using the content of the present application specification, or directly or indirectly used in other related technical fields, is also included in the patent protection scope of the present application.
Claims
1. A high-toughness steel-concrete interface adhesive, characterized in that, It contains the following components in parts by weight: 90-110 parts epoxy resin matrix, 15-30 parts curing agent, 10-25 parts toughening agent, 30-60 parts filler, 0.2-2 parts hollow fiber, and 0.5-2 parts corrosion inhibitor.
2. The steel-concrete interface adhesive according to claim 1, characterized in that, The corrosion inhibitor is loaded onto hollow fibers.
3. The steel-concrete interface adhesive according to claim 2, characterized in that, The corrosion inhibitor is at least one of molybdate or phosphate.
4. The steel-concrete interface adhesive according to claim 1, characterized in that, The hollow fiber has a length of 100-200 μm.
5. The steel-concrete interface adhesive according to claim 1, characterized in that, The hollow fiber is made of polyester, polypropylene, or polyamide.
6. The steel-concrete interface adhesive according to claim 1, characterized in that, The filler includes quartz sand and silica fume, wherein the particle size of the quartz sand is 60-80 μm and the particle size of the silica fume is 10-30 μm.
7. The steel-concrete interface adhesive according to claim 1, characterized in that, The curing agent is a polyamide or a modified amine curing agent.
8. The steel-concrete interface adhesive according to claim 1, characterized in that, The toughening agent is at least one of carboxyl-terminated butadiene-acrylonitrile rubber and polyurethane prepolymer.
9. A method for preparing the steel-concrete interface adhesive as described in any one of claims 1-8, characterized in that, Includes the following steps: S1. Preparation of resin matrix: The epoxy resin matrix and toughening agent are mixed in an organic solvent and stirred until homogeneous; S2. Filler dispersion: Add filler to the mixture obtained in step S1 and stir until homogeneous; S3. Fibers and corrosion inhibitors and dispersion: Add hollow fibers and corrosion inhibitors to the mixture from step S2 and stir until uniformly dispersed; S4. Curing reaction: Add curing agent and stir until uniform.
10. The preparation method according to claim 9, characterized in that, In step S3, the hollow fibers are immersed in a liquid corrosion inhibitor to load the corrosion inhibitor onto the fibers. Then, the treated hollow fibers are added to the mixture from step S2 and stirred until uniformly dispersed.